2019
DOI: 10.3389/fenrg.2019.00143
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dioxide Capture From Internal Combustion Engine Exhaust Using Temperature Swing Adsorption

Abstract: In order to reduce the CO 2 emissions in the transportation sector, one can electrify the vehicle, switch to biofuel, or capture and store CO 2 on board. In this study, integration of an on board CO 2 capture and storage unit with an internal combustion engine has been proposed. The technology can be applied for various internal combustion or Stirling engines with targeted applications in the transportation sector. Truck transport for goods delivery is used as an example for on board CO 2 capture and storage s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(30 citation statements)
references
References 35 publications
(40 reference statements)
0
30
0
Order By: Relevance
“…Being more efficient, an SOFC results in lower carbon emissions during use. In this aspect, an integration of ICE with a temperature swing adsorption (TSA) for onboard CCS in the transportation sector has been proposed (Sharma and Maréchal, 2019), where it was reported that 90% of the CO 2 emitted from combustion of on-board fuels can be captured without any energy penalty. Such a system is adequately applied for train and ship transports (Sharma and Maréchal, 2019).…”
Section: Bio-carbon Circularity In Automotive and Distributed Powermentioning
confidence: 99%
See 1 more Smart Citation
“…Being more efficient, an SOFC results in lower carbon emissions during use. In this aspect, an integration of ICE with a temperature swing adsorption (TSA) for onboard CCS in the transportation sector has been proposed (Sharma and Maréchal, 2019), where it was reported that 90% of the CO 2 emitted from combustion of on-board fuels can be captured without any energy penalty. Such a system is adequately applied for train and ship transports (Sharma and Maréchal, 2019).…”
Section: Bio-carbon Circularity In Automotive and Distributed Powermentioning
confidence: 99%
“…SOFC systems using hydrocarbons have been found to have electrical efficiencies (LHV-basis) in the order of 60%(van Biert et al, 2020). Here, a conservative estimate of 45% has been taken for TTW efficiency, to account for losses in the electric motors, CO 2 compression for storage on-board, and any other losses Sharma and Maréchal (Sharma and Maréchal, 2019). state an electrical energy cost of 0.88 MJ for compressing 2.11 kg of CO 2 (equivalent to 1.398 L ethanol) up to 75 bar.…”
mentioning
confidence: 99%
“…Assuming 10 kWh per liter 41 as lower heating value of diesel, out of which 3.6 kWh of energy converted in mechanical power to drive the vehicle, 3.8 kWh is wasted in the exhaust gas and 2.6 kWh goes to the coolant. 18,42 If MEA is selected as a solvent in the absorber column, the exhaust gas must be water-cooled to 30 C for maximum absorption with MEA. 43 The energy released during this process can be calculated with the same procedure as followed by Hossain et al 42 and found to be 1.169 kWh.…”
Section: Energy Balance Analysismentioning
confidence: 99%
“…Battery-operated vehicles have been advised for the reduction of CO 2 emission from the transportation sector but it is associated with the penalty of the electric density stored in the batteries and the establishment of charging infrastructure. 18,19 The swing adsorption technique used by Sharma et al 18 for capturing the CO 2 from heavy-duty internal combustion engine has integrated temperature swing absorption, Rankine cycle, heat pump, and CO 2 compression and liquefaction which requires significant modification of the engine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation